Analysis Of Instructional Methods Used In Secondary School On Environmental Learning - Ayu Lestari; Ashadi Ashadi; Maridi Maridi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
The use of instructional method is very important for education. The Appropriate instructional methods for the characteristics of learning materials will help teachers and students reach the targeted aim of competencies. This research aims to analyze the use of instructional methods used in secondary school on environmental learning. This analysis is very useful in giving real-representatives potrait and the impact of the use of instructional methods toward students’ performance. Data were analyzed qualitatively in accordance with the Miles &Huberman. The data collection methods are an observation of learning activity, indepth interviews with teachers and student learning outcomes documentation in SMP 13 Magelang, one of developing secondary schools in Indonesia. The results showed that the use of instructional methods has not been suitable for characteristics of the learning materials and students’ characteristics. Teachers should choose instructional methods that will make easier for students to understand the concept. Instructional methods that are often used by teachers is lecture and discussion method. The result is poor performance of student learning. The root cause of the mismatch instructional method with the characteristics of material is insufficient time allocation that will affect teacher’s teaching and learning strategy